TEACHING METHODOLOGY OF COMPETITIVE GIANT SLALOM TECHNIQUE IN ALPINE SKING - Rašid Hadžić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2009)
Teaching competitive giant slalom technique, mostly, should be developed by using appropriate playgrounds where particular curve phases are extra marked witu clear signs (markers). Playgrounds are very important in learning competitive technique process. They enable speed dosing aud CHOICE of ideal sking line. Playground`s position should be different, dependinig on what we want to learn. In playground`s position we should obey certain rules: - bigger distance in playground for lower position - bigger playground expance for biger swaying amplitude - smaller distance and smaller expance for bigger frequency Such playground`s position, appropriate for terrain, enable us a total control of tasks which competitors have to prform. We choose harder position when competitors overcome all important elements of technique in casier conditions. When moving from training to situational placed paths, me should obey basic rules of gradual weight incre- asing aud at tve same time returning to simple easy positions.